IMPROVE YOUR ENGLISH LEVEL WITH CHATGPT - Marjona Tursunqulova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. The provided article illustrates how to make better your English level with ChatGPT.Also,the researcher will make a discussion about cost-effective boons of utilizing ChatGPT in order to achieve success in English.In the following paragraphs we will introduce ChatGPT,what are the benefits of AI in education and useful strategies of ChatGPT to enhance English level.